1997
DOI: 10.1103/physrevlett.78.2827
|View full text |Cite
|
Sign up to set email alerts
|

Decay Free Microwave Magnetic Envelope Soliton Pulse Trains in Yttrium Iron Garnet Thin Films

Abstract: Microwave magnetic envelope soliton pulse trains with no decay in amplitude have been obtained in magnetic films for the first time. The solitons were formed from magnetostatic spin waves with negative dispersion, or backward volume waves, propagated in a long and narrow 5.2 mm thick yttrium iron garnet film strip biased at 1096 Oe. An interrupted feedback technique was used to produce the soliton pulse trains from an initial 25 ns wide input pulse at a carrier frequency of 5.0 GHz. The train extended for over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…2 and 3 mirror and extend previous results for single peaked solitons. [3][4][5][6] These studies have shown that, when there is appropriate compensation between the dispersion and the nonlinear response, one can form a robust and non-dispersive bright MME soliton with a CP profile across the peak. Constant phase, therefore, provides a simple unambiguous criterion for bright MME soliton formation.…”
Section: A Spatial Evolutionmentioning
confidence: 97%
See 1 more Smart Citation
“…2 and 3 mirror and extend previous results for single peaked solitons. [3][4][5][6] These studies have shown that, when there is appropriate compensation between the dispersion and the nonlinear response, one can form a robust and non-dispersive bright MME soliton with a CP profile across the peak. Constant phase, therefore, provides a simple unambiguous criterion for bright MME soliton formation.…”
Section: A Spatial Evolutionmentioning
confidence: 97%
“…More specifically, Ref. 3 and later papers [4][5][6] show that single MME soliton pulses have a constant phase (CP) profile across the center part of the pulse. It is expected that multipeaked soliton (MPS) entities should also have peaks with a CP character.…”
Section: Introductionmentioning
confidence: 99%
“…(1) in [10] ]. For the experimental parameters, one obtains a theoretical soliton pulse width at half amplitude of 19.7 ns, which is in good agreement with the measured width of 20 ns.…”
mentioning
confidence: 99%
“…Based on the nonlinear Schrödinger equation model (see, e.g., [3]), f 0 is equal to u 0 y g p jN͞Dj͞p, where u 0 is the signal amplitude. For D 520 cm 2 ͞rad s, N 29.9 3 10 9 rad͞s, and u 0 0.014, determined in the same way as in [10], f 0 is about 43 MHz. From theory, the maximum frequency width for the modulational instability zone is equal to 2f 0 or 86 MHz.…”
mentioning
confidence: 99%
See 1 more Smart Citation